Market Survey Of The Atorvastatin (Antihypertensive) - RAHUL G. JANGAM; NITIN B. LONDHE; DR. RAJESH J.OSWAL; REEMA A. KAMBLE (International Journal of Pharma and Bio Sciences, 2011)
The market survey of Atorvastatin (Antihypertensive drug) was conducted in Pune and Mumbai region. The various brands of Atorvastatin are Storvas, Tonact, Atorva, TG-Tor, Aztor, Atorlip, Zivast, Xtor, Atorfit, Stator, Avas, Atormac, Modlip, Atheart, Lipikind and Atorec are available in selected areas. The Storvas is more prescribed by doctors. The highest selling brand of Atorvastatin is Strovas. According to medical survey it shows that Atorvastatin (Ranbaxy) is highest selling brand in Mumbai region compare to Pune region. Atorvastatin is good Antihypertensive drug.